A non-invasive combined strategy to improve the appropriateness of upper gastrointestinal endoscopy - Rodriguez, Kryssia; Franceschi, Marilisa; Ferronato, Antonio; Brozzi, Lorenzo; Antico, Antonio; Panozzo, Maria Piera; Massella, Arianna; Pertoldi, Barbara; Morini, Alice; Barchi, Alberto; Russo, Michele; Crafa, Pellegrino; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim Increasing the appropriateness of upper gastrointestinal endoscopy (UGIE) improves the quality of care while containing costs. The aim of this study was to improve the appropriateness of UGIE through a process involving evaluation of prescriptions and the use of a non-invasive alternative. Materials and methods A senior endoscopist evaluated the appropriateness of all outpatient referrals for UGIE and established the proper timing. Referrals were either accepted and programmed, canceled, or substituted by a non-invasive evaluation of gastric function, determining serum levels of gastrin-17 (G17), Pepsinogen I (PGI) and II (PGII), and antibodies against Helicobacter pylori. Results A total of 5102 requests for UGIE examinations were evaluated; 540 (10.4%) were inappropriate and had been prescribed for: gastroesophageal reflux disease (n=307), surveillance with erroneous timing (n=113), dyspepsia (n=66), other indications (n=20), and absence of written indication (n=34). Gastric function was evaluated in 282/540 patients; findings included normal values in 94 patients without proton-pump inhibitor therapy (PPI) and in 48 on PPI, active H pylori infection in 56, previous H pylori infection in 30, GERD in n=50, and atrophic gastritis in n=4. UGIE was performed in the latter 4 cases. Within 2 years (range 1-22 months) of the initial refusal, 105/504 patients underwent UGIE, with normal endoscopic findings in 71/105 (67.5%), and with no cases of cancer. Conclusions This strategy, based on a strict control of prescriptions, is effective to increase the appropriateness while containing public health costs. The use of gastric function testing improves patient selection for UGIE endoscopy.